TINJAUAN YURIDIS PERJANJIAN SEWA BELI KENDARAAN BERMOTOR MELALUI PEMBAYARAN ANGSURAN DALAM JAMINAN FIDUSIA - Jacklyn Alona Br Bangun; Fatimah Az-Zahra; Triya Anggraini; Rouli Lumban batu; Iren Br Bangun; Vivin Silvia Boang Manalu; Parlaungan Gabriel Siahaan; Sri Hadiningrum (CV Rewang Rencang, 2024)
Motor vehicle hire purchase agreements with installment payments under fiduciary guarantees are an important topic in the context of civil law. Problems that often occur include violations of agreements, the debtor's lack of understanding of the contents of the agreement, and the practice of forcibly withdrawing vehicles without a valid legal process. This research method uses normative legal analysis by referring to applicable laws and regulations, literature studies, and various related sources of information. The results of the research show the legal rules that apply to parties who violate the agreement, legal protection efforts for debtors, as well as procedures for valid withdrawal of vehicles by creditors in the context of motor vehicle rental purchase agreements with installments in fiduciary guarantees.